Rancang Bangun Model Alat Monitoring Pada Refrigerasi Tabung Vorteks - Hadimi, Hadimi; Karyadi, Edi; Rusadi, Rusadi (Politeknik Negeri Pontianak, 2024)
This research was conducted to design and create a model of a vortex tube refrigeration system monitoring tool that will be used as a practicum medium in the Refrigeration and Air Conditioning Engineering course. Currently, the cooling system used as a practical medium is a vapor compression cooling system. The goal to be achieved in this research is a model of a monitoring tool for vortex tube refrigeration techniques. With this monitoring model, it is hoped that it can be used to carry out practical work on vortex tube refrigeration techniques. The stages of this research start from the design stage, assembly stage and functional testing and data acquisition stages. With research flow; preparation of tools and materials, making monitoring models of vortex tube refrigeration engineering tools, testing tool models, collecting and processing data from model experiments. This monitoring tool model for Vortex Tube Refrigeration can directly monitor things such as; Flow rate, temperature, air pressure and COP, all data is recorded and stored on the SD card. The higher the pressure, the cooler the cold air produced, this is because the vortex tube compresses the air. The highest COP value is 0.31 which occurs at the standard 3 bar setting with v1 and v2 (72 and 61 m3/s), P1 and P2 (1.8 and 0.28 bar).